On the Naming of Lake Sevan as Gökcha - Galichian, (Galchian) R. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
In any given part of the world, forced demographic changes to the ethnic population inevitably result in changes to the local linguistics as well as the evolution and alteration of toponyms. The resulting changes can give politicians and extremists the possibility to exploit the changes to augment their claims and incursions. In extreme cases, such as the “scorched earth” policy adopted by Shah Abbas of Iran in the so called “protectorates” of Nakhchivan, Syuniq and Karabakh, the Armenian ethnic population was decimated. The elimination of the ethnic Armenians gave an opportunity to the Turkish speaking remaining minority of the local population the possibility to claim ownership of these lands. Through the citation of historical facts and cartographic evidence, the article discusses the reasons for the naming of Lake Sevan in Armenia as “Gokcha”, and the exploitation of this new toponym in an attempt to prove ownership of the lake, through the presentation of dubious documents and arguments.
Keywords: Cartography; Toponymy; History